فاعلية الطباق في الإيقاع الداخلي في شعر أبي تمام (Journal of Hama University, 2025)
The research seeks to study the effectiveness of counterpoint in the internal rhythm in Abu Tammam’s poetry. It begins with an introduction that he devotes to the meaning of the term and in which he presents the opinions of some ancient critics. Then he devotes the applied study to researching the ability of counterpoint to highlight the internal rhythm of the text. By studying the phonetically similar and semantically opposite morphological forms, and by researching this type in Abu Tammam’s collections, the study found that it can be divided into: chromatic counterpoint, and kinetic counterpoint (vertical, horizontal).The research demonstrated, through what these two features represented, the ability of counterpoint to raise the tempo of the internal music of the text, and its role did not stop only at the limits of sound and rhythm; It is not merely a repetition of sounds for a decorative purpose, but rather it extends beyond that to meaning. By contributing to revealing the psychological and suggestive connotations of the poet.